Depth In Providing Banking Credit In Support Improving Village Creative Industries In Langkat District - Meigia Nidya Sari; Junawan, Junawan; Annisa Fajariah Damanik (CV. AFDIFAL MAJU BERKAH, 2024)
The national development carried out so far is a development effort sustainability in order to create a just and prosperous society based on Pancasila and the 1945 Constitution. In order to achieve this goal, implementation development must always pay attention to harmony, harmony and balance various elements of development, including in the banking sector. This research aims to deepen the provision of banking credit to support industrial improvement creative village in Langkat Regency. The population used in this research is employees at PT. BRI (Persero) in Langkat Regency. Sampling technique with using saturated samples. The sample size was 30 people. Types of data in this research are primary and secondary data. Data collection techniques use questionnaires, interviews, and documentation studies with data analysis techniques using approaches quantitative with statistical tools of multiple linear regression analysis. The research results show: 1) Internal control has a partially insignificant effect on effectiveness granting credit, 2) Internal audit has a partially significant effect on effectiveness granting credit, 3) Internal control and internal audit have a significant effect simultaneously on the effectiveness of providing credit, namely 83.3%.